Effects of proton pump inhibitor use on the esophageal microbial community - Sadia Tasnim; Aaron L. Miller; Daniel C. Jupiter; Catherine F. Hamilton; Gabriel L. Reep; Timothy S. Krill; Richard B. Pyles; Ikenna C. Okereke (BMC Gastroenterology, 2020)
Abstract Background Changes in the esophageal microbiome correlate with esophageal disease, but the effects of proton pump inhibitor (PPI) drugs are incompletely characterized. Our objective was to identify the effects of PPI use on the microbial community of the esophagus. Methods Mucosal biopsies of the distal esophagus were analyzed using a customized esophageal microbiome qPCR panel array (EMB). Patient demographics, use of PPIs, duration of use and dose were recorded. Results Fifty-eight patients were included. Mean age was 60.5 years. Ninety percent (52/58) of patients were on PPIs. Mean dose was 42.7 mg. Mean duration of use was 2.5 years. The use of PPIs led to a significant difference in absolute levels of only one organism, Actinomyces, in the entire array (p < 0.01). Among patients who used proton pump inhibitors, there was no significant association between dose and absolute levels of any organism. Similarly, there was no association between duration of use and absolute levels of any organism. Conclusions PPI use does not seem to cause significant changes in the distal esophageal microbial community. Future studies with larger sample sizes and esophageal pH testing should be performed to determine the level of acidity and its relationship to the microbial community.